The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/bcp.14546
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular adverse events associated with hydroxychloroquine and chloroquine: A comprehensive pharmacovigilance analysis of pre‐COVID‐19 reports

Abstract: There is a clinical need for safety data regarding hydroxychloroquine (HCQ) and chloroquine (CQ) during the coronavirus (COVID-19) pandemic. We analysed realworld data using the U.S. Food and Drug Administration Adverse Events Reporting System (FAERS) database to assess HCQ/CQ-associated cardiovascular adverse events (CVAEs) in pre-COVID-19 reports. Methods: We conducted disproportionality analysis of HCQ/CQ in the FAERS database (07/2014-9/2019), using reporting odds ratio (ROR) and the lower bound of the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 42 publications
(96 reference statements)
2
32
0
Order By: Relevance
“…Finally, the increased number of reports of QT prolongation underlines the importance of carefully considering potential drug-drug interactions and cardiac comorbidities during treatment with (hydroxy)chloroquine. 20 Our results also showed reports involving (hydroxy)chloroquine use during pregnancy in the first pandemic time interval with a peak in March 2020. Indeed, this could be related to the overall increased awareness of (hydroxy)chloroquine safety.…”
Section: Discussionsupporting
confidence: 83%
“…Finally, the increased number of reports of QT prolongation underlines the importance of carefully considering potential drug-drug interactions and cardiac comorbidities during treatment with (hydroxy)chloroquine. 20 Our results also showed reports involving (hydroxy)chloroquine use during pregnancy in the first pandemic time interval with a peak in March 2020. Indeed, this could be related to the overall increased awareness of (hydroxy)chloroquine safety.…”
Section: Discussionsupporting
confidence: 83%
“…Fourth, as a recent study suggested a risk of cardiac arrhythmias with hydroxychloroquine, we performed a head-to-head comparison (remdesivir versus hydroxychloroquine). [ 7 ] In addition, to address the effect of age and sex, we used stratification analyses according age groups (≤44 years, 45-64 years and ≥ 65 years) and sex.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent clinical review and research are needed to assess causality. In addition to the known ADEs for HCQ, such as higher rates of cardiovascular event reports, 15 we found evidence of ADEs related to herpes simplex hepatitis, vessel puncture site hemorrhage, and a prolonged electrocardiogram QRS complex. Likewise, several ADEs related to the use of AZM were found.…”
Section: Discussionmentioning
confidence: 54%